Influence of the top slag layer on the flow dynamics in AC-electric arc furnaces. (20th January 2011) - Ramirez-Argaez, M.A.; Conejo, A.N.; Guzman, Y.I.C.; Trapaga, G.
A mathematical model describing fluid flow for an industrial three-phase electric arc furnace has been developed which involves two-immiscible liquids in the computational domain and the main driving force for the movement is due to buoyancy forces. Comparison between the case where only liquid steel occupies the entire computational domain and the case of two-phases has been also carried out. The influence of slag physical and thermal properties on fluid flow and heat transfer is included in this work. The results of this work provide a clear description of flow patterns in the presence of the top slag layer. It has been found a marked effect of the slag phase to decrease the velocity patterns of liquid steel.